Integrating Central Venous and Arterial Line Placement Training for Respiratory Therapists: A Sustainable Strategic Approach to Enhance Patient Care - Rebecca McClay; Orlando Garner; Ashley Pyle; Gerardo Catalasan; Michael Mileski (Critical Care Research and Practice)
Conclusions: We found the integration of RTs to the vascular access role to be highly successful in meeting both facility and patient needs.